Delirium and Psychiatric Sequelae Associated to SARS-CoV-2 in Asymptomatic Patients With Psychiatric History and Mild Cognitive Impairment as Risk Factors: Three Case Reports - Fabrazzo, Michele; Russo, Antonio; Luciano, Mario; Camerlengo, Alessio; Catapano, Pierluigi; Amoroso, Bianca; Catapano, Francesco; Coppola, Nicola (Frontiers in Psychiatry, 2022)
Human coronaviruses have neuroinvasive and neurotropic abilities that might explain neuropsychiatric outcomes in affected patients. We hypothesized that delirium might be the sole clinical manifestation or even the prodrome of a psychopathological episode consistent with the mental history of a few infected patients with a diagnosed cognitive impairment. We examined three patients with preexisting mild cognitive impairment and delirium at admission for suspected SARS-CoV-2 infection. We diagnosed delirium using DSM-5 and Confusion Assessment Method (CAM) and measured consciousness level by the Glasgow Coma Scale. All the patients had no history of fever, respiratory complications, anosmia or ageusia, meningitis and had negative cerebrospinal fluid analysis for SARS-CoV-2. Our first patient had no neuropsychiatric history, the second reported only a depressive episode, and the third had a history of bipolar disorder dated back to forty years before. In the first patient, delirium resolved two days following the admission. The other two patients recovered in 4 and 14 days, and delirium appeared as the prodrome of a new psychiatric episode resembling past events. Clinicians should monitor the possibility that SARS-CoV-2 presence in the brain might clinically manifest in the form of delirium and acute psychiatric sequelae, even without other systemic symptoms. Neuropsychiatric history and cognitive impairment are to be considered as predisposing factors for COVID-19 sequelae in delirium patients.